Multi-omics analysis of DNA replication-associated primase polymerase (PRIMPOL) in pan-cancer: a potential target for prognosis and immune response - Langmei Deng; Abhimanyu Thakur; Jinwu Peng; Liying Song; Zhilan Li (European Journal of Medical Research, 2023)
Abstract Background It is critical to understand the mechanisms of human cancers in order to develop the effective anti-cancer therapeutic strategies. Recent studies indicated that primase polymerase (PRIMPOL) is strongly associated with the development of human cancers. Nevertheless, a systematic pan-cancer analysis of PRIMPOL remains to be further clarified. Method Comprehensive multi-omics bioinformatics algorithms, such as TIMER2.0, GEPIA2.0 and cBioPortal, were utilized to evaluate the biological roles of PRIMPOL in pan-cancer, including the expression profiles, genomic alterations, prognostic values and immune regulation. Results PRIMPOL was upregulated in glioblastoma multiforme and kidney renal clear cell carcinoma. The brain lower grade glioma patients with enhanced PRIMPOL expression displayed poor prognostic values. We also demonstrated the PRIMPOL's immunomodulating effects on pan-cancer as well as its genomic changes and methylation levels. The aberrant expression of PRIMPOL was linked to various cancer-associated pathways, including DNA damage response, DNA repair, and angiogenesis, according to single-cell sequencing and function enrichment. Conclusions This pan-cancer analysis offers a thorough review of the functional roles of PRIMPOL in human cancers, suggesting PRIMPOL as a potentially important biomarker for the progression and immunotherapy of various cancers.